DESMOID TUMOR :: A CASE REPORT - SAKOLCHAIPONG, Kulthida; BOONJUNWETWAT, Darunee; PUNYAVORAVUT, Voranuch (The ASEAN Journal of Radiology, 2023)
Extra-abdominal fibromatosis (desmoid tumor) is an uncommon soft tissue tumor. About two-third of cases occur in the extremities. We present a female 43-yearold case of multicentric desmoid tumor.